How Concrete Language Shapes Customer Satisfaction - Packard, Grant; Berger, Jonah (Journal of Consumer Research, 2021)
Consumers are often frustrated by customer service. But could a simple shift in language help improve customer satisfaction? We suggest that linguistic concreteness—the tangibility, specificity, or imaginability of words employees use when speaking to customers—can shape consumer attitudes and behaviors. Five studies, including text analysis of over 1,000 real consumer–employee interactions in two different field contexts, demonstrate that customers are more satisfied, willing to purchase, and purchase more when employees speak to them concretely. This occurs because customers infer that employees who use more concrete language are listening (i.e., attending to and understanding their needs). These findings deepen understanding of how language shapes consumer behavior, reveal a psychological mechanism by which concreteness impacts person perception, and provide a straightforward way that managers could help enhance customer satisfaction.